A juvenile turtle (Testudines, Eucryptodira) from the Upper Jurassic of Langenberg Quarry, Oker, Northern Germany. (10th December 2013) - Jansen, Maren; Klein, Nicole; Angielczyk, Kenneth
Abstract Turtles are frequently found in fluviatile to lagoonal and shallow marine sediments in the Upper Jurassic of Western Europe. These turtles usually show a mixture of basal and derived characters, but phylogenetic relationships are still largely unresolved. This is mainly due to the incompleteness of fossils and the lack of taxonomically unambiguous characters and is also related to the presence of different ontogenetic stages, which are not easy to compare. The morphological description of a new turtle from the Upper Jurassic of Langenberg Quarry (Oker, Lower Saxony, Germany) gives further insights into the ontogeny of basal eucryptodire turtles as well as into aquatic adaptation of Upper Jurassic turtles. The specimen is herein left in open nomenclature, due to the fact that it represents a juvenile individual. Several characters define the specimen as juvenile: its small size (7.28 cm carapace length); lateral carapacial fontanelles; enlarged vertebral scutes; a radial striation pattern covering the entire carapace; and the grade of ossification of preserved skull and limb elements. A clear aquatic adaptation of the individual is the elongated manus, a feature that is independent of ontogenetic age. The elongated manus may indicate a marine lifestyle and the individual possibly inhabited nearshore to offshore areas around the former Jurassic islands, which today form the Saxony Basin. The ossification pattern of the carapace of this eucryptodire turtle resembles that of known Jurassic paracryptodires and thus provides new insights to the ontogeny of Jurassic turtles.